Radiological Risks From Potential Exposure of the Population to Radiation From Orphan Radioactive Sources. Issue 5 (May 2019) - Tsilikis, Ioannis; Pantos, Ioannis; Zouliati, Ifigeneia; Koutras, Antonios; Kalinterakis, Georgios; Syllaios, Athanasios
Abstract : Abstract: People in their everyday lives are exposed to radiation. Natural radiation is emitted from space, subsoil, and various materials which contain radioactive materials. Humans are also exposed to radiation from medical and industrial applications that use radioactive sources with artificial radioactive materials. Such radioactive sources may nevertheless get out of the control system and become orphan sources. Because these radiation sources are usually contained within metal shields such as lead and iron, the shields can end up as scrap metal being used in the metallurgical industry as raw material. Incidents have been recorded around the world, and several are reported in the literature and described here, where orphan sources have caused direct radiation exposure and/or environmental and personal contamination when the sources leaked. Timely and prompt recognition of an orphan radioactive source or device is crucial in order to minimize the radiological risk and its implications for the general population.